The natural history of gastro‐oesophageal reflux symptoms in the community and its effects on survival: a longitudinal 10‐year follow‐up study. Issue 3 (29th November 2012) - Ford, A. C.; Forman, D.; Bailey, A. G.; Axon, A. T. R.; Moayyedi, P.
Summary Background Gastro‐oesophageal reflux symptoms (GERS) are common in the community. However, few studies have examined their long‐term natural history, or impact on survival. Aim To examine these issues in individuals recruited into a community‐based screening programme for Helicobacter pylori in 1994. Methods Data on mortality and cause of death at 10 years were obtained from the Office for National Statistics. Baseline demographic data, lifestyle factors, gastrointestinal symptoms and quality of life were recorded at study entry. The effect of all these factors on persistent and new‐onset GERS, and 10‐year mortality, were examined using univariate and multivariate analysis, with results expressed as odds ratios (ORs) or hazard ratios (HR) with 99% confidence intervals (CI). Results Of 3967 individuals providing complete GERS data at baseline and 10 years, 549 (13.8%) had GERS at baseline. Of these, 183 (33.3%) had persistent symptoms. Among 3418 individuals asymptomatic at baseline, approximately 0.8% per year developed new‐onset GERS. No predictors of persistent GERS were identified. New‐onset symptoms were associated with lower quality of life or presence of irritable bowel syndrome (IBS) at baseline, and higher body mass index (BMI) at 10 years. There were 8331 (99.1%) of 8407 subjects providing complete GERS data at baseline, 1289 (15.5%) of whom were symptomatic. Presence of GERS at baseline did not affect survival (HR: 0.84; 99% CI: 0.44–1.59). Conclusions Gastro‐oesophageal reflux symptoms persisted in one‐third of individuals, whilst new‐onset gastro‐oesophageal reflux symptoms were associated with poor quality of life, irritable bowel syndrome and higher body mass index. Gastro‐oesophageal reflux symptoms did not impact adversely on survival.